2020
DOI: 10.1111/lam.13280
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and in vitro screening of Fructobacillus fructosus MCC 3996 isolated from Butea monosperma flower for probiotic potential

Abstract: The fructophilic bacterium Fructobacillus fructosus MCC 3996 described in the present investigation was isolated from the nectar of Butea monosperma flower and evaluated in vitro for the manifestation of probiotic features. The strain utilizes fructose faster than glucose and is capable to grow in the range of 1–35% fructose concentration (optimum 5% w/v) and thus denotes its fructophilic nature. In vitro assessments of the strain have examined for the endurance in acidic environment/gastric juice, the better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In fact, it was interesting to note that many of the taxa shown to be positively correlated with honey production include flower-associated species, e.g. Apilactobacillus, Fructobacillus fructosus, Acinetobacter boissieri, Neokomagataea [48][49][50][51][52]. This increased prevalence and abundance in the microbiome is potentially reflective of increased nectar gathering and, consequently, increase in honey productionalthough a role in promoting hive productivity cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was interesting to note that many of the taxa shown to be positively correlated with honey production include flower-associated species, e.g. Apilactobacillus, Fructobacillus fructosus, Acinetobacter boissieri, Neokomagataea [48][49][50][51][52]. This increased prevalence and abundance in the microbiome is potentially reflective of increased nectar gathering and, consequently, increase in honey productionalthough a role in promoting hive productivity cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [ 104 ] suggested that F. fructosus MCC 3996 could be suitably prescribed during antibiotic therapy using oxacillin and streptomycin, as the strain showed resistance against these two antibiotics. In accordance, all F. fructosus in our study were found to be resistant to oxacillin but also sensitive or intermediate to streptomycin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to L. mesenteroides, Kalparasa had Fructobacillus fructosus and G. oxydans in good abundance. F. fructosus (F. fructosus MCC 3996), like Leuconostoc, had also been isolated from the nectar of Butea monosperma flower already reported for its probiotic potential (Patil et al, 2020). Fructophilic LAB from such fruits and flower sources were found to possess probiotic potential in ameliorating fructose-mediated irritable bowel syndrome (Sakander et al, 2019).…”
Section: Discussionmentioning
confidence: 99%